Comparative Efficiency of Motor Fuels and Electricity for Automobile Transport - Mazurova, Olga Vasilevna (Economy of Regions, 2019)
The article presents estimates regarding the scale of changes arising from the mass introduction of electric vehicles. The relevance of this paper is determined by the increasing demands for the environmental cleanliness of transport energy sources. It is obvious that in the future alternative fuel vehicles will crowd out oil fuel transport. I propose an original approach to the economic evaluation of the alternative resources’ use in transport taking into account regional conditions and initial data’s uncertainty. It allows comparing new technologies in transport and choosing the most efficient options for power supply of passengers and freight vehicles in the country’s different regions. The main feature of the proposed model is the combination of optimization and simulation methods based on the Monte Carlo technique. The study identifies the trends in the dynamics of motorization and the structure of energy resources in the transport sector and assesses the possible consequences of the electric vehicles’ introduction in Russia. It also includes the results of experimental calculations using various combinations of expected conditions and forecasting prices in accordance with the demand for motor fuel in major macro regions of Russia. The article has demonstrated that the economic efficiency of the use of alternative fuels and energy in transport will depend on regional characteristics, in particular, on the dynamics of changes in prices for energy resources. The proposed methodological approach and the results obtained can be useful in studying the problems of the power industry development.